T-lymphocytes from focused ultrasound ablation subsequently mediate cellular antitumor immunity after adoptive cell transfer immunotherapy - Ran, Li-Feng; Xie, Xun-Peng; Xia, Ji-Zhu; Xie, Fang-Lin; Fan, Yan-Min; Wu, Feng (Frontiers in Immunology, 2023)
Background: Our previous studies found that high-intensity focused ultrasound (HIFU) stimulated tumor-specific T cells in a mouse H22 tumor model, and adoptive transfer of the T cells from HIFUtreated mice could subsequently elicit stronger inhibition on the growth and progression of the implanted tumors. The aim of this study was to investigate the mechanism of T cells from focused ultrasound ablation in HIFU-mediated immunomodulation. Methods: Sixty H22 tumor-bearing mice were treated by either HIFU or sham-HIFU, and 30 naïve syngeneic mice served as controls. All mice were euthanized on day 14 after HIFU and splenic T cell suspensions were obtained in each group. Using an adoptive cell transfer model, a total of 1 × 10 6 T cells from HIFU treated-mice were intravenously injected into each syngeneic H22 tumor-bearing mouse twice on day 3 and 4, followed by the sacrifice for immunological assessments at 14 days after the adoptive transfer. Results: T cells from HIFU-treated mice could significantly enhance the cytotoxicity of CTLs (p < 0.001), with a significant increase of TNF-α (p < 0.001) and IFN-γ secretion (p < 0.001). Compared to control and sham-HIFU groups, the number of Fas ligand + and perforin + tumor-infiltrating lymphocytes (TILs) and apoptotic H22 tumor cells were significantly higher (p < 0.001) in the HIFU group. There were linear correlations between apoptotic tumor cells and Fas ligand + TILs (r = 0.9145, p < 0.001) and perforin + TILs (r = 0.9619, p < 0.001). Conclusions: T cells from HIFU-treated mice can subsequently mediate cellular antitumor immunity, which may play an important role in the HIFU-based immunomodulation.